The association of public health interventions regarding both infant sleep position and pertussis immunization with sudden infant death syndrome rates: an ecological study - Jacqueline Müller-Nordhorn; Amir Hakimhashemi; Stefan N. Willich; Sylvia Binting; Thomas Keil (BMC Pediatrics)
Abstract Background Infections may play a role in the etiology of sudden infant death syndrome (SIDS), with Bordetella pertussis being a potential agent. The objective was to analyze the association of SIDS and infant pertussis hospitalization rates over time, comparing a previously unvaccinated population (West Germany) versus a predominantly vaccinated population (East Germany). Methods We calculated SIDS rates per 1000 live births per state. Live births and SIDS were available from 1980 onwards for the West German states and from 1991 onwards for the East German states. We applied interrupted time series (ITS) analyses to investigate the role of two public health interventions in 1991 (West Germany) and in 2000 (West and East Germany), respectively. Infant pertussis hospitalizations were available for five West German and three East German states between 1994 and 2019. We used multilayer and multivariate correlation analyses to determine the correlation between SIDS and pertussis hospitalization rates, including Pearson correlation test and vector autoregressive (VAR) analysis. Results In West Germany, the average annual SIDS rate (per 1000 live births) increased from 1.08 in 1980 to 1.68 in 1991, before declining to 1.18 in 1992 and subsequently to 0.10 in 2020. In East Germany, the average annual SIDS rate (per 1000 live births) decreased from 0.79 in 1991 to 0.12 in 2020. The results of the ITS model indicated a significant change in both level and slope at the 1991 interventions (West Germany) and in slope at the 2000 interventions (West and East Germany). The correlation coefficients between SIDS and infant pertussis hospitalization rates were 0.69 (95% CI [confidence interval] 0.41, 0.85; p  < 0.001) in West Germany, and 0.41 (95% CI 0.03, 0.69; p = 0.037) in East Germany. The correlation decreased during later periods (2000–2019, 2010–2019), particularly in East Germany. The results of the VAR analysis corroborated the findings of the main analyses. Conclusions SIDS and infant pertussis hospitalization rates were correlated in both West and East Germany. Further studies – including improved diagnostic assessment of pertussis – seem warranted. Clinical trial number Not applicable.